CRITIQUE JURIDIQUE DE L’EFFECTIVITÉ DE LA LUTTE CONTRE LES CHANGEMENTS CLIMATIQUES EN RÉPUBLIQUE DÉMOCRATIQUE DU CONGO A TRAVERS LE DISPOSITIF LÉGAL DE GESTION DE LA BIODIVERSITÉ. – Cas du Code de Conservation de la nature -- - CHALACHALA BONGALA, Nadyne-Clémence (IJRDO Journal of Forestry, wild life and Environment, 2019)
The Democratic republic of Congo contains about 155.5 billions of hectares of timber, I mean sixteen seventh percent of his whole land scale, those contain 99 billions of hectares of rain forest, within most ecosystems having an High Conservation Value(HCV).  But we have to note that deforestation and degradation of forest must be considered in certain regions, especially around Kinshasa and other big towns. In the Congo basin, forests are the major source of subsistence and benefits for the both formal and non formal sectors. An amelioration in the protection and the management of forests is an essential part of the response that the DRC has to give the climate change, according to the adaptation and the attenuation objectives.Climate changes question calls necessary all actors efforts in order to let down its effects which needs more attentions.